Small molecule of sphingosine as a rescue of dopaminergic cells: A cell therapy approach in neurodegenerative diseases therapeutics. Issue 7 (8th January 2019) - Tavakol, Shima; Hoveizi, Elham; Tavakol, Behnaz; Azedi, Fereshteh; Ebrahimi‐Barough, Somayeh; Keyhanvar, Peyman; Joghataei, Mohammad Taghi
Abstract: Multiple sclerosis (MS) patients should take medication such as fingolimod (FTY‐720) for a long time, hence pharmaceutical effects on other neural cells such as dopaminergic cells are important. Dopaminergic cell line, BE(2)‐M17, was treated by FTY‐720 and then cell viability and genes involve in neurosurvival were investigated. It was disclosed that FTY‐720 significantly stimulates Bcl2 overexpression. Whereas, it decreased intracellular reactive oxygen species production and cell membrane damage of dopaminergic cells. The increase in Bcl2/Bax ratio increased the cell metabolic activity and decreased propidium iodide‐positive cells. Besides, FTY‐720 induced the overexpression of CACNA1C, nNOS gene, and nitric oxide production. However, FTY‐720 induced GABARA1 overexpression and eventually it could overcame to the cytotoxic effect of intracellular calcium. This cascade led to tyrosine hydroxylase and BDNF genes overexpression whereas FTY‐720 did not change GDNF concentration in BE(2)‐M17 cells. Concluding, it might be said that taking FTY‐720 in MS patients did not induce adverse effect on dopaminergic cells. Abstract : FTY‐720 as a Food and Drug Administration approved drug for multiple sclerosis (MS) involved in BDNF stimulation and patients who suffer from MS should take medication for a long time. Hence, the effects of their medications on other cells in their body are important. Our results showed that not only FTY‐720 had no adverse effect on dopaminergic cells but also rescue them from oxidative stress and increases their cell viability.